Fish waste as Biofertilizer / Nur Husnina Hadzeri - Hadzeri, Nur Husnina (2018)
Plant growth depends on the nutrient uptake from its surrounding mainly from the soil. Applying fertilizer in order to replace the nutrient loss due to uptake by plant may enhance the plant growth. Fish waste contains macronutrients that are necessary for the growth of plant. This research aimed to determine the Nitrogen (N), Phosphorus (P) and Potassium (K) concentration in fish waste biofertilizer. Based on the proximate analysis obtained, N, P and K concentratior rvere recorded as 14.8 ± 1.2 mg/g, 10.0 ± A.9 mg/g and 14.1 ± 1.5 mg/g respectively. The concentration of these macronutrients was found to give a positive impact on growth of Mustard throughout the period of 9 weeks. Mustard that receive teafrnent with fish waste had recorded higher total average height of plant total average length of leaf and total average number of leaves of 10.8 cm, 10.2 cm and 7.0 respectively than unfertilized Mustard. Thus, fish waste can be an eftctive biofertilizer to plant.